2022
DOI: 10.1136/archdischild-2022-324227
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use in ambulatory care for acutely ill children in high-income countries: a systematic review and meta-analysis

Abstract: ObjectiveTo determine the rate and appropriateness of antibiotic prescribing for acutely ill children in ambulatory care in high-income countries.DesignOn 10 February 2021, we systematically searched articles published since 2000 in MEDLINE, Embase, CENTRAL, Web Of Science and grey literature databases. We included cross-sectional and longitudinal studies, time-series analyses, randomised controlled trials and non-randomised studies of interventions with acutely ill children up to and including 12 years of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…The overprescribing of antibiotics for acute respiratory tract infections in the paediatric population is still common, raising the public health concern of antibiotic resistance [ 40 ]. A meta-analysis on the prevention of acute URTIs has shown that infants and children supplemented with probiotics had a 41% lower risk of being prescribed antibiotics compared to placebo [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overprescribing of antibiotics for acute respiratory tract infections in the paediatric population is still common, raising the public health concern of antibiotic resistance [ 40 ]. A meta-analysis on the prevention of acute URTIs has shown that infants and children supplemented with probiotics had a 41% lower risk of being prescribed antibiotics compared to placebo [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the infant and pediatric populations from high income setting, antibiotic prescription rates in acute care exceed 35%, many in the first 30 days of life ( 9 ), whereas antibiotic prescription rates exceed 45% in outpatient care ( 12 ). As such, close to half of all children will be exposed to antibiotics during critical windows of development.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, antibiotic prescribing rates in children with AOM are high. A recent systematic review analyzing the use of antibiotics in ambulatory care for acutely ill children in high-income countries, including the UK, reported the antibiotic prescribing rate for AOM was 85.6% (95% confidence interval, CI 73.3–92.9%) [ 12 ]. As a result, the National Institute for Health and Care Excellence (NICE) guideline for AOM antimicrobial prescribing was updated in March 2022 to aim to limit antibiotic use and reduce antimicrobial resistance [ 13 ].…”
Section: Introductionmentioning
confidence: 99%